Solution (1):
Given:
Multiplying y = 3x - 5 by 2:
y = -6x - 5
y = -6x - 5
Adding both equations:
Dividing 3 both sides:
Substitute the value of y into any equation.
- y = -6x - 5
- => -5 = -6x - 5
- => 0 = -6x
Divide -6 both sides.
Solution (2):
Given:
Add both the equations.
y = -8x + 7
Divide 2 both sides.
- 2y = -2
- => 2y/2 = -2/2
- => y = -1
Substitute the value of y into any equation.
Add 9 both sides.
- => -1 + 9 = 8x - 9 + 9
- => 8 = 8x
Divide 8 both sides.
Solution (3):
Given:
Reorganize the first equation.
- -x + 6y = 21
- => 6y = x + 21
Multiply the first equation by 5.
y = -5x + 12
y = -5x + 12
Add both the equations.
Divide 31 both sides.
- 31y = 117
- => 31y/31 = 117/31
- => y = 117/31
Substitute the value of y into any equation.
- -x + 6y = 21
- => -x + 6(117/31) = 21
- => -x + 702/31 = 651/31
Subtract 702/31 both sides.
- => -x = 651/31 - 702/31
- => -x = -51/31
- => x = 51/31